2017
DOI: 10.1111/imre.12354
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Membership in a World of Global Migration: (How) Does Citizenship Matter?

Abstract: This article synthesizes the literature on citizenship and immigration to evaluate the heft of citizenship and theorize why it matters. We examine why citizenship laws vary cross‐nationally and why some immigrants acquire citizenship while others do not. We consider how citizenship influences rights, identities, and participation and the mechanisms by which citizenship could influence lives. We consider frameworks, such as cultural and performative citizenship, that de‐center legal status and the nation‐state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 134 publications
(180 reference statements)
3
48
2
1
Order By: Relevance
“…It contributes to the literature by delineating what citizenship in the country of residence means and to whom naturalization matters the most (cf. Bloemraad and Sheares 2017). The analysis showed that the interviewees assigned three meanings to citizenship, albeit in differing degrees.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It contributes to the literature by delineating what citizenship in the country of residence means and to whom naturalization matters the most (cf. Bloemraad and Sheares 2017). The analysis showed that the interviewees assigned three meanings to citizenship, albeit in differing degrees.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Selecting groups who tend to naturalize in high numbers limits the possibility of generalizing (in a non-statistical sense) the findings to immigrants in general. Previous research has shown that citizenship in the country of residence seems to matter less to immigrants from developed, Western countries since they already hold valuable citizenships (Bevelander et al 2015;Bloemraad and Sheares 2017;Vink, Prokic-Breuer, and Dronkers 2013). Furthermore, most of the denizens interviewed were not denizens by choice but by constraint; they wanted to naturalize but were legally ineligible because of insufficient identity documentation (a requirement to naturalize).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…A number of IMR articles tackle foundational concepts like citizenship, examining how residential concentration and naturalization rates are linked (Abascal 2017) or offering synthetic overviews of citizenship scholarship in migration studies (Bloemraad and Sheares 2017). Others grapple with popular concepts like "crisis" in public discourse around international migration, highlighting the political work such terms do while also showing how a 'crisis' might feel quite ordinary to migrants already experiencing chronic and slowly unfolding 'crises' of their own (Bylander 2018).…”
Section: International Migration Review 87mentioning
confidence: 99%